Acidose láctica ruminal aguda induzida experimentalmente em ovinos: estudo clínico e laboratorial - Sabes, Amanda Festa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The sheep meet industry is constantly rising in Brazil and this fact leads to an increase on the number of confined animals, looking for greater weight gain in short period of time. This situation predisposes to disorders such as acute lactic ruminal acidosis (ARLA) and, consequently, acute laminitis, which causes economic problems by the treatment costs, reduced productivity and disposal of animals. Ten adult sheep were induced to ALRA by oral administration of sucrose; were further evaluated to physical examination, arterial blood gas analysis, hematological parameters, glucose and lactate plasma, serum protein profile and zymography for detection of metalloproteinases 2 and 9. All animals had clinical signs of ARLA, the respiratory rate remained high up to 36 hours, returning to normal in 48 hours. Five animals showed typical clinical signs of acute laminitis, however clinical treatment was not necessary. The values of the red blood cell count, packed cell volume, hemoglobin, total leukocytes and neutrophils and segmented rod rases in 24 hours. Glucose content increased up to eight hours by increasing the synthesis of volatile fatty acids and subsequent blood absorption; lactate has increased to 24 hours, with a subsequent decrease. From four hours there was an increase of pH, bicarbonate and base excess. After 12 hours, the animals had metabolic acidosis. At 28 hours there was normalization of the hemogasometry parameters without need of treatment. In serum protein were identified 13 proteins: immunoglobulins A (IgA) and G (IgG), ceruloplasmin (Cp), transferrin (Tf), albumin (Ab), 1-antitrypsin ( 1AT), haptoglobin (Hp), 1- acid glycoprotein ( 1GA), 95 (MWP95), 46 (MWP46), 36 (MWP36) and 31 (MWP31) kDa molecular weight protein In all animals with ARLA the total protein showed changes from 08 hours, coinciding with clinical signs of dehydration, which occurred up to 36 hours after induction. Although five animals shown clinical ...

A ovinocultura de corte está em constante ascensão no Brasil e tal fato leva ao aumento do número de animais confinados, visando maior ganho de peso em curto período de tempo. Tal situação predispõe os ovinos a desordens como acidose láctica ruminal aguda (ALRA) e, consequentemente, laminite aguda, as quais geram problemas econômicos pelos custos do tratamento, menor produtividade do rebanho e descarte de animais. Dez ovelhas adultas foram induzidas à ALRA através da administração oral de sacarose; posteriormente foram avaliadas quando ao exame físico além das análises hemogasométricas arteriais, hematológicas, avaliação da glicose e lactato plasmáticos, proteinograma sérico e zimografia para detecção das metaloproteinases 2 e 9. Todos os animais tiveram sinais clínicos de ALRA, a frequência respiratória permaneceu elevada até às 36 horas, retornando à normalidade com 48 horas. Cinco animais apresentam sinais clínicos característicos de laminite aguda, porém não foi necessária a realização de tratamento clínico. Os valores da contagem de hemácias, volume globular, hemoglobina, leucócitos totais e neutrófilos bastonetes e segmentados elevaram-se nas 24 horas. Os teores de glicose aumentaram até as 8 horas pelo aumento da síntese dos ácidos graxos voláteis e posterior absorção sanguínea; o lactato apresentou aumento até as 24 horas, com posterior diminuição dos valores. A partir de 4 horas ocorreu elevação do pH, bicarbonato e excesso de base. Após 12 horas, os animais apresentaram acidose metabólica. Com 28 horas houve normalização dos parâmetros hemogasimétricos, sem necessidade de tratamento. No proteinograma sérico foram identificadas 13 proteínas: imunoglobulinas A (IgA) e G (IgG), ceruloplasmina (Cp), transferrina (Tf), albumina (Ab), 1-antitripsina ( 1AT), haptoglobina (Hp), 1-glicoproteína ácida ( 1GA), 95 (PPM95), 46 (PPM46), 36 (PPM36) e 31 (PMM31) kDa proteínas de...
Keywords: Ovino; Ovelha; Gasometria; Laminite; Metaloproteinase 2 da matriz; Metaloproteinase 9 da Matriz; Acidose; Sheep